Attempted caveolae-mediated phagocytosis of surface-fixed micro-pillars by human osteoblasts. (January 2016) - Moerke, Caroline; Mueller, Petra; Nebe, Barbara
Abstract: Cells are sensitive to their underlying micro- and nano-topography, but the complex interplay is not completely understood especially if sharp edges and ridges of stochastically modified surfaces interfere with an attached cell body. Micro-topography offers cues that evoke a large range of cell responses e.g. altered adhesion behavior and integrin expression resulting in disturbed cell functions. In this study, we analyzed why osteoblastic cells mimic the underlying geometrical micro-pillar structure (5 × 5 × 5 μm, spacing of 5 μm) with their actin cytoskeleton. Interestingly, we discovered an attempted caveolae-mediated phagocytosis of each micro-pillar beneath the cells, which was accompanied by increased intracellular reactive oxygen species (ROS) production and reduced intracellular ATP levels. This energy consuming process hampered the cells in their function as osteoblasts at the interface. The raft-dependent/caveolae-mediated phagocytic pathway is regulated by diverse cellular components including caveolin-1 (Cav-1), cholesterol, actin cytoskeleton as well as actin-binding proteins like annexin A2 (AnxA2). Our results show a new aspect of osteoblast–material interaction and give insight into how cells behave on extraordinary micro-structures. We conclude that stochastically structured implants used in orthopedic surgery should avoid any topographical heights which induce phagocytosis to prevent their successful ingrowth.